OPTIMIZING CASH WAQF EDUCATION IN PROMOTING COMMUNITY WELFARE USING COMMUNITY BASED RESEARCH - Ilahi, Muhammad Redo; Afrianty, Nonie; Bahril, Muthi’ ‘Adilah (Reinforce: Journal of Sharia Management, 2024)
Waqf is one of the Islamic financial instruments with great potential, which can improve people's life quality. The purpose of this Community Service activity is to provide education about cash waqf to employees of the Religious Affairs Office of North Seluma District. In order to overcome the problems of the activities, researchers are taking steps to carry out direct socialization (face to face). The method of this community service is Community Based Research (CBR). The implementation of this community service activity is carried out by training using the lecture method in delivering material and pre-test and post-test methods as an effort to explore employees' level of understanding of the material presented before and after in accordance with indicators of increasing understanding. Based on the community service activities carried out, it can be concluded that the service program designed by the researcher has been implemented according to plan. Researchers obtained data from 15 KUA employees that changed significantly between before and after conducting cash waqf education for employees of the North Seluma District Religious Affairs Office. Employees of the North Seluma District Religious Affairs Office have knowledge about cash waqf and have the intention to start conducting cash waqf.